Assessment Of The Sheep Production Management Systems Of Small-Scale Farmers In The Maluti-A-Phofung Local Municipality Of The Eastern Free State - Sankatane, Mahlako, Richard. (Central University of Technology, Free State, 2018)
The purpose of this project was to evaluate small-scale farmers’ management of sheep production systems in the Eastern Free State. Primary data were collected from 40 small-scale farmers using questionnaires in the study area and the results were analysed using a descriptive analysis model. The results indicate that the majority of the respondents (35 or 87.5%) were male, and five (12.5%) were female. This indicates the general farming demographics of the regions. The results also showed that only 32.5% had a tertiary education. Parameter estimates are indicated from low education levels and a lack of farming skills pertaining to livestock production (with only 42.5% of the farmers having adequate skill levels); poor management skills in terms of nutritional and health management (only 57.5% supplied supplemented feeding prior to lambing); high transportation costs (48% of farmers did not own transportation to the market); lack of market information (66% of the farmers actively marketed their product); and poor delivery of support services from the government as only 45% of farmers surveyed received support services from government. It was also evident that the majority of the farmers did not have the most basic equipment i.e. dosing gun, syringe and castration equipment. The findings also showed that 34% of the respondents suffered from a lack of market information owing to poor communication, tools, and support services from the government and extension officers. The majority of the farmers relied on word of mouth, family, and own research for information regarding product prices, which in most cases was biased, inaccurate, and/or out-dated. The study recommends that the government must host planned workshops for all farmers in order to equip them with knowledge. Short courses should be provided to small-scale farmers, furthermore, support must be provided through training activities, and business counselling must be given to the farmers and farm managers in the Eastern Free State.